Arctic & antartic vol. 1 [videorecording]. (Eyewitness, vol. 1, 1996)
Arctic and antartic explores the life and legends of these harshly beautiful polar kingdoms. Journey to the ends of the earth climate presents its greatest challenge to survival, and meet the remarkable animals that choose to live out in the cold.